Associations between Difficulty in Accessing Maternal and Child Health Services and Stress Responses among Mothers Raising Young Children during the COVID-19 Pandemic in Japan - Noriko Toyama; Chikako Hokama; Misuzu Takahara; Yuko Toyama (MDPI AG, 2024)
In Japan, maternal and child health (MCH) services were canceled or limited during the COVID-19 pandemic, potentially damaging the mental health of mothers raising young children. This study aimed to examine associations between difficulty in accessing MCH services and various stress responses among such mothers in Japan. An Internet-based questionnaire survey was conducted in November 2022 targeting mothers raising young children who had registered with a Japanese online research company (n = 1032). The questionnaires included items from the Public Health Research Foundation Stress Checklist (Short Form) (PHRF-SCL(SF)), sociodemographic variables, and questions about difficulty accessing MCH services due to COVID-19. Chi-squared tests and multivariate logistic regression analysis were performed. In total, 45.7% of mothers experienced difficulty in accessing MCH services due to COVID-19. Mean PHRF-SCL(SF) scores were 4.9 for anxiety, 7.3 for tiredness, 2.8 for autonomic symptoms, and 5.2 for depression. These scores indicated worse stress responses than the general population and mothers raising young children before the COVID-19 pandemic. Mothers who experienced difficulty in accessing MCH services due to COVID-19 were 1.47-1.53 times more likely to be associated with high stress responses (PHRF-SCL(SF) scores). Given the difficulty mothers faced accessing MCH services due to COVID-19 and the negative impact this had, careful follow-up and support are necessary for mothers affected by the COVID-19 pandemic.